2023
DOI: 10.1097/md.0000000000033229
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets and mechanisms involved in the action of Banxia Shumi decoction in insomnia treatment

Abstract: Insomnia is a common sleep-wake rhythm disorder, which is closely associated with the occurrence of many serious diseases. Recent researches suggest that circadian rhythms play an important role in regulating sleep duration and sleep quality. Banxia Shumi decoction (BSXM) is a well-known Chinese formula used to treat insomnia in China. However, the overall molecular mechanism behind this therapeutic effect has not yet been fully elucidated. This study aimed to identify the molecular targets and mechanisms invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Prescriptions containing BX have been shown to improve sleep. [ 56 ] Among them, the combination of BX and XKC is known as Shuangxia Decoction (SXD). Zhang et al [ 57 ] found that SXD effectively improves sleep quality in fruit flies.…”
Section: Discussionmentioning
confidence: 99%
“…Prescriptions containing BX have been shown to improve sleep. [ 56 ] Among them, the combination of BX and XKC is known as Shuangxia Decoction (SXD). Zhang et al [ 57 ] found that SXD effectively improves sleep quality in fruit flies.…”
Section: Discussionmentioning
confidence: 99%